2020
DOI: 10.4028/www.scientific.net/kem.860.69
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gadolinium Ion Doping on Electronic Conductivity of LiFePO<sub>4</sub>/C

Abstract: In the recent years, LiFePO4 has been widely developed as a cathode for lithium ion batteries because it has high theoretical capacity (170 mAh/g), good stability and is also environmentally friendly. However, the poor electronic conductivity (~10-9 S/cm) and low diffusion coefficient of lithium ion (~10-15-10-14 cm2/s) are limiting its application. Some solutions to overcome this problem are carbon coating and doping metal ions. This study aims to determine the effect of Gd3+ ion doping on the electronic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…379 However, Molenda et al 380 observed small increases in conductivity with Al 3+ , Zr 4+ , and W 6+ substitution of 25% atom and recently, a small increase in conductivity (less than one order of magnitude) was observed by gadolinium substitution into LFP. 381 Overall, there is evidence that partial metal substitutions can effectively enhance the electrochemical performance of LFP, specifically increasing the reversible capacity and rate performance, but often at the cost of reduced longterm stability and the particles must be coated with a conductive material to cycle effectively. Complete metal substitution has been shown to yield materials of high theoretical energy densities.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…379 However, Molenda et al 380 observed small increases in conductivity with Al 3+ , Zr 4+ , and W 6+ substitution of 25% atom and recently, a small increase in conductivity (less than one order of magnitude) was observed by gadolinium substitution into LFP. 381 Overall, there is evidence that partial metal substitutions can effectively enhance the electrochemical performance of LFP, specifically increasing the reversible capacity and rate performance, but often at the cost of reduced longterm stability and the particles must be coated with a conductive material to cycle effectively. Complete metal substitution has been shown to yield materials of high theoretical energy densities.…”
Section: Review Materials Advancesmentioning
confidence: 99%